2006
DOI: 10.1007/s10591-006-9003-1
|View full text |Cite
|
Sign up to set email alerts
|

Associated Factors of Suicide Among University Students: Importance of Family Environment

Abstract: The aim in this study was to underline the importance of family environment as a significant associate of suicide probability among university students. For this aim 226 Turkish university students completed Suicide Probability Scale, Family Environment Questionnaire, Beck Depression Inventory, and Positive and Negative Affect Scale. As a result of the formulated regression analysis, after controlling for the 51% of the total variance accounted for by the control variables (i.e., gender, age, living with famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 26 publications
2
9
0
1
Order By: Relevance
“…Specifi cally, the fi rst distinct feature refers to depressive symptoms, social anxiety, fears of abandonment in signifi cant interpersonal relationships, and loneliness; the second distinct feature refers to the confi dence in others and the degree of comfort with intimacy. This characterization is supported in the literature that mentions signifi cant diff erences in various psychological and psychopathological domains between individuals with and without suicidal ideation (Borges & Werlang 2006;Dervic et al, 2007;Eisenberg et al, 2007;Ellis & Ratliff , 1986;Eskin, Voracek, Stieger, & Altinyazar, 2011;Garlow et al, 2008;Gençöz & Or, 2006;Kashden, Fremouw, Callahan, & Franzen 1993;Lasgaard et al, 2010;Mazza & Reynolds, 2001;Özer, Yildirim, & Erkoç, 2015;Peter et al, 2008;Reinherz, Tanner, Berger, Beardslee, & Fitzmaurice, 2006;Tyssen, Vaglum, Grønvold, & Ekeberg, 2001).…”
Section: Discussionsupporting
confidence: 61%
“…Specifi cally, the fi rst distinct feature refers to depressive symptoms, social anxiety, fears of abandonment in signifi cant interpersonal relationships, and loneliness; the second distinct feature refers to the confi dence in others and the degree of comfort with intimacy. This characterization is supported in the literature that mentions signifi cant diff erences in various psychological and psychopathological domains between individuals with and without suicidal ideation (Borges & Werlang 2006;Dervic et al, 2007;Eisenberg et al, 2007;Ellis & Ratliff , 1986;Eskin, Voracek, Stieger, & Altinyazar, 2011;Garlow et al, 2008;Gençöz & Or, 2006;Kashden, Fremouw, Callahan, & Franzen 1993;Lasgaard et al, 2010;Mazza & Reynolds, 2001;Özer, Yildirim, & Erkoç, 2015;Peter et al, 2008;Reinherz, Tanner, Berger, Beardslee, & Fitzmaurice, 2006;Tyssen, Vaglum, Grønvold, & Ekeberg, 2001).…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, the cut-off values were not used to assign a diagnosis or treatment, but rather to inform decisions about whether a more comprehensive clinical screening should be undertaken (Zimmerman, 2002). The high levels of symptoms present on the subscales is consistent with previous research that indicated that not only globally, but also locally, there is an increase in mental health problems amongst students (Del Pilar, 2009;Garlow et al, 2008;Gencoz & Or, 2006;Pillay et al, 2002). The recommendation for follow-up was most prominent regarding post-traumatic stress, alcohol abuse/dependency and major depression.…”
Section: Resultssupporting
confidence: 58%
“…Hence, international research has indicated an upward trend over the last few decades in the quantity and severity of mental health problems presented by HE students (Del Pilar, 2009;Garlow et al, 2008;Gencoz & Or, 2006;Wang, Lee & Wahid, 2013). These studies demonstrated significant levels of depressive symptoms, suicide ideation, suicide attempts, anxiety, anger, and alcohol and drug use in students.…”
Section: Introductionmentioning
confidence: 99%
“…Suicidal Possibility Scale (SPS) was used to measure individual levels of suicide risk (Cull et al, 1988), which can be recognized as another gold standard for evaluating the performance of the Chinese suicide dictionary. SPS is an effective screening tool designed to assess suicide risk in adolescents and adults (Gençöz, 2006;Naud, 2010). SPS consists of 36 self-rating items.…”
Section: Measurementmentioning
confidence: 99%